Євген Маланюк на шпальтах польського часопису «Biuletyn Polsko-Ukraiński» (Варшава 1932-1938) - Кравченко, Світлана Іванівна; Kravchenko, Svitlana I. (Львівська національна наукова бібліотека України імені В. Стефаника, 2009)
У статті розглядаються публіцистичні та літературно-критичні тексти Євгена Маланюка, які друкувалися впродовж 1932-1938 рр. на сторінках польського тижневика «Biuletyn Polsko-Ukraiński», їх ідейно-тематична спрямованість, критерії та підходи до оцінки суспільно-культурних явищ.

The article “Evhen Malanjyk on the columns of polish newspaper “Bjyletun Polsko-Ykrajinski”(Warsaw 1932-1938) ” is about publicist and literary-critical texts by Evhen Malanjyk, which were published on the columns of polish newspaper “Bjyletun Polsko-Ykrajinski” during 1932-1938 years. Also it is about high-minded and thematic direction of literary-critical texts by Evhen Malanjyk and criterions, points of view on opinions of social-culture facts.
Keywords: статті; виступи; рецензії; огляди; полеміка; articles; speeches; reviews; polemics